Reduction of spillover effects on independent modal space control through optimal placement of sensors and actuators. (2nd July 2015) - Cinquemani, S; Ferrari, D; Bayati, I
Abstract: The independent modal space control (IMSC) technique can be profitably used to suppress vibration in flexible structures by increasing the damping of the modes involved, without changing the corresponding natural frequencies and modal shapes. Reducing vibration means reducing the associated noise and enhancing the performance of the system and its fatigue durability. The main limitations of this approach are related to spillover effects due to the dynamics of unmodeled modes. This work investigates analytically how spillover effects in IMSC are closely related to the number and the position of thesensors and actuators involved, in addition to the reduced model adopted to synthesize the control itself. The performance of the IMSC technique is optimized by means of genetic algorithms to reduce spillover effects, finding the best placements for sensors and actuators. Theoretical aspects are supported by numerical simulations.